The Influence of Parents' Social Support on Student Learning Independence at SMAN 1 Maros - Prasiwi, Aron Erlangga; Razak, Ahmad (Polteknik Ilmu Pemasyarakatan, 2025)
Students in high school have a central role in developing their own academic, social, and personal potential, as well as in shaping their future vision and goals. However, it is important to understand that the role of students in the educational process is not only limited to receiving information from teachers and textbooks but students must also have strong learning independence. The aim of this research is to determine the influence of parental social support on student learning independence at Sman 1 Maros. The sample in this research was 272 students. Data collection used research instruments, namely, the parental social support scale and the learning independence scale. Hypothesis testing using Spearman Rho analysis. The results of the research show that there is an influence of parental social support on student learning independence at Sman 1 Maros. This research has a low level of correlation with an r value of 0.244 with a significance value of 0.000. Therefore the existing hypothesis is accepted. There is an influence of parental social support on students' learning independence at Sman 1 Maros. It is hoped that parents will support this and that students will be able to increase their learning independence at schoo.